The Effect of Work Initiative, Technology Mastership, and Work Environment on Employee Performance at PT PLN (Persero) - Huda, Miftahul; Trisnawati; Helmi, Sulaiman; Roni, Mukran (Sinergi International Journal of Management and Business, 2024)
Performance is the result of work that can be achieved by a person or group of people in a company following their respective duties and responsibilities to achieve company goals legally, not against the law, and following morals and ethics. The success of Pt PLN (Persero) Customer Service Implementation (Up3) Palembang Customer Service Unit (ULP) Rivai in carrying out its duties must be connected to its employees, who are the technical implementers of the policy. In other words, the position of employees is one of the determining factors for smoothness in realizing company goals. Based on the data obtained at Pt PLN (Persero) Customer Service Implementation (UP3) Palembang Customer Service Unit (ULP) Rivai, the performance of employees in 2023 did not reach the target set by the company due to several factors that affected employee performance. One way to improve employee performance is to conduct a performance appraisal, which shows how well a person or group has worked to achieve company goals. Using a quantitative descriptive approach with a sample of 95 respondents and assisted by the SmartPLS 4.1.0.6 application, this study assesses employee performance from three components: work initiative, mastery of technology, and work environment. The result of this study indicates that the work initiative variable has a positive and significant effect on employee performance, the technology mastery variable has a positive and significant impact on employee performance, and the work environment has a positive and significant effect on employee performance.